2005
DOI: 10.1007/s00497-005-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression and thermotolerance of calreticulin during pollen development in tobacco

Abstract: Glycoproteins 50, 55, 59 and 64 kDa with affinity to the lectin ConA occurring abundantly in mature tobacco pollen were shown to exhibit high tolerance against heating at 90°C for 30°min. The 59 kDa glycoprotein (GP59) was isolated by affinity chromatography on ConA-agarose followed by 2D-electrophoresis and identified by MS analysis as tobacco calreticulin with approximate pI 4.2. Identification of the protein was confirmed by immunoblotting with human anti-calreticulin and by labelling with a specific dye fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Western blotting showed that the 64 kDa polypeptide is a member of the HSP60 family (Singh and Lakhotia, 2000). Glycoproteins 64 kDa with affinity to the lectin ConA may be involved in pollen heat tolerance in tobacco ( Nicotiana tabacum L.) (Hrubá et al, 2005). It has been reported that 42 kDa proteins induced in the cytoplasm in Saccharomyces cerevisiae form ordered oligomers with a barrel‐like structure and act as a chaperone either in vivo or in vitro, which suppressed the aggregation of one‐third of the cytosolic proteins ((Haslbeck et al, 2004; Haslbeck, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting showed that the 64 kDa polypeptide is a member of the HSP60 family (Singh and Lakhotia, 2000). Glycoproteins 64 kDa with affinity to the lectin ConA may be involved in pollen heat tolerance in tobacco ( Nicotiana tabacum L.) (Hrubá et al, 2005). It has been reported that 42 kDa proteins induced in the cytoplasm in Saccharomyces cerevisiae form ordered oligomers with a barrel‐like structure and act as a chaperone either in vivo or in vitro, which suppressed the aggregation of one‐third of the cytosolic proteins ((Haslbeck et al, 2004; Haslbeck, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, a wider examination of expressed transcripts and proteomic data in pollen (Hruba et al, 2005;Sheoran et al, 2006) and other tissues (Swanson et al, 2005) may aid in identifying specific protein candidates for such calcium binding; information about such products is likely to be readily available for bioinformatic data mining in international genome and proteome related databases. This calcium store is dynamic and may therefore be readily converted to (and from) free calcium through interaction with a wide variety of control proteins-in this sense such proteins have calmodulinlike properties.…”
Section: Types Of Calcium In Cellsmentioning
confidence: 99%
“…However, Eady et al (1994) reported that both tricellular pollen of Arabidop.9is and bicellular pollen of Nicotiana took 8 d to progress from the microspore stage to anther opening under greenhouse conditions. Since both have dehydrated pollen (Johnson and McCormick, 2001;Hrubá et al, 2005), development of tricellular pollen in Arabidopsis appears to be accelerated relative to bicellular pollen in Nicotiana (Fig. 5).…”
Section: Discussion mentioning
confidence: 92%